Hypoxia-induced microRNA-590-5p promotes colorectal cancer progression by modulating matrix metalloproteinase activity. (1st March 2018) - Kim, Chan Woo; Oh, Eun-Taex; Kim, Joon Mee; Park, Jin-Seok; Lee, Don Haeng; Lee, Jae-Seon; Kim, Kyung Keun; Park, Heon Joo
Abstract: Hypoxia leads to cancer progression and promotes the metastatic potential of cancer cells. MicroRNAs (miRNAs) are small non-coding RNA that have emerged as key players involved in cancer development and progression. Hypoxia alters a set of hypoxia-mediated miRNAs expression during tumor development and it may function as oncogenes or tumor-suppressors. However, the roles and molecular mechanisms of hypoxia-regulatory miRNAs in colorectal cancer (CRC) progression remain poorly understood. Here we firstly identified miR-590-5p as hypoxia-sensitive miRNAs which was upregulated in colon cancer cells under hypoxia. Hypoxia-induced miR-590-5p suppressed the expression of RECK, in turn, promoting cell invasiveness and migratory abilities via activation of matrix metalloproteinases (MMPs) and filopodia protrusion in vitro . Inhibition of miR-590-5p suppressed tumor growth and metastasis in mouse xenograft and CRC liver metastasis models via inhibition of MMPs activity. Clinical analysis revealed higher miR-590-5p expression in CRC, compared to normal specimens. Furthermore, miR-590-5p expression was significantly increased in liver metastasis as compared to their matched primary CRC. Taken together, our findings provide the first evidence that miR-590-5p may have potential as a therapeutic target for CRC patients with metastasis. Highlights: MiR-590-5p is hypoxia-sensitive miRNAs which was upregulated in colon cancer cells under hypoxia. Hypoxia-induced miR-590-5p enhanced matrix metalloproteinase activity by targeting RECK. Inhibition of miR-590-5p suppressed tumor growth and metastasis in vivo . miR-590-5p is more upregulated in human liver metastasis tissues, compared to primary CRC. Targeting of hypoxia-induced miR-590-5p may provide an effective therapeutic approach to inhibit CRC progression.